Social skills groups for children and adolescents with Asperger's syndrome : a step-by-step program - Painter, Kim Kiker (Kimberley Kiker), 1977- (JKP resource materials., 2006)
Social Skills Groups for Children and Adolescents with Asperger Syndrome is an empirically-grounded, ready-to-use curriculum for clinicians, teachers and other professionals wishing to lead social skills groups for children and adolescents with AS. It provides an introduction to AS and issues surrounding social skills, including diagnostic and assessment issues, the importance of good social skills, and treatment approaches. At the heart of the resource is a practical, user-friendly, fully photocopiable program, consisting of 10 core sessions and 13 supplementary sessions, which covers topics.